HUBUNGAN ANTARA PANJANG TUNGKAI DAN POWER OTOT TUNGKAI DENGAN HASIL LARI 100 METER PADA SISWA KELAS VIII SMPN 1 PRAYA TENGAH TAHUN PELAJARAN 2016/2017 - Hairunnisha Hairunnisha; Mujriah Mujriah; Adi Suriatno (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The running speed of the sprint number is determined by the length of step and step frequency as stated by Jonath (1986: 58) that "Running speed is the product of the length and frequency (number per second) of the step, who wants to run fast should make the move longer and make many lebig steps every second, From the above explanation, the researcher is interested to conduct research with the title Relationship Between Limb Length And Limb Muscle Power With Results Running 100 Meters In Students Class VIII SMPN 1 Praya Tengah Lesson 2016/2017. With the formulation of the problem is Is There a Relationship Between Limb And Muscle Limb Power With Results Running 100 Meters In Students Class VIII SMPN 1 Praya Tengah Lesson 2016/2017. The aim is to find out whether there is a relationship between limb length and limb muscle power With 100 Meter Running Results In Grade VIII Students SMPN 1 Praya Tengah Lesson 2016 / 2017.Sampel sample in this study amounted to 30 people because in this study examines all the characteristics that exist in the population which is called the study population study. In the data processing the researchers used multiple linear correlation statistics formula. Based on the results of data analysis obtained r - count value of 0.637 while the value of r-table with a significant level of 5% indicates the number of 0.361 this means that 0.637> 0.361 or in other words the value of r-count obtained greater than the limit of rejection of null hypothesis (Ho) listed in table value r. to reject the null hypothesis (Ho) required the value of t-count equal to or greater than the value of r-tabel.From the results of data analysis above, it can be concluded that "There is a Relationship Between Limb Length And Muscle Limb Power With 100 Meter Running Results in students class VIII SMPN 1 Praya Tengah academic year 2016/2017 ".